Oral Corticosteroid Relieves Post-COVID-19 Anosmia in a 35-Year-Old Patient - Sam K. Touisserkani; Azin Ayatollahi (Case Reports in Otolaryngology)
Coronavirus disease 2019 (COVID-19) is a highly infectious respiratory illness caused by SARS-CoV-2. Not much is yet known about this new viral disease. In our early encounter with the COVID-19, before the pandemic and during the early days of dealing with this novel viral disease in our country, we saw some cases of anosmia in patients infected by SARS-CoV-2. In many cases, this chemosensitive dysfunction persisted after the negativization of the nasopharyngeal swab. We report effective treatment of anosmia by oral corticosteroid therapy in a patient recovered from COVID-19.